The Relationship Between Metabolic Syndrome, Its Components, and Erectile Dysfunction: A Systematic Review and a Meta-Analysis of Observational Studies. (1st June 2015) - Besiroglu, Huseyin; Otunctemur, Alper; Ozbek, Emin
Abstract: Introduction: The studies examining the association between metabolic syndrome (MetS), its components, and erectile dysfunction (ED) should be reevaluated to arrive at comprehensive results in this field. Aim: Our aim was to gather individual studies in order to achieve a more reliable conclusion regarding the relationship between MetS, its components, and ED. Methods: Three investigators searched the Pubmed-Medline and Embase databases using the key words "metabolic syndrome" and "erectile dysfunction." The individual studies were evaluated for selection of suitable studies. Main Outcome Measures: Eight studies that met all inclusion criteria were chosen, and a pooled analysis of odds ratio (ORs) between MetS and ED was calculated. The components of MetS to ED were also estimated. Results: Eight observational studies with a total of 12, 067 participants were examined. The overall analysis revealed a 2.6-fold increase in patients with MetS having ED (2.67[1.79–3.96]; P < 0.0001). All individual components of MetS except high-density lipoprotein level were also found to correlate with an increased prevalence of ED. Of those, fasting blood sugar was detected highest rate for ED with OR of 2.07 ([1.49–2.87]; P < 0.0001). Conclusions: Metabolic syndrome is associated with a high risk rate of ED, and patients with MetS should be informed about this association and encouraged to make lifestyle modifications to improve their general health and to limit cardiovascular risk as well as ED prevalence. However, manuscripts included in meta-analysis were observational studies that prohibits ascertainment of temporal associations and necessitates further prospective studies.